2020
DOI: 10.3390/biomedicines8120584
|View full text |Cite
|
Sign up to set email alerts
|

NURR1 Alterations in Perinatal Stress: A First Step towards Late-Onset Diseases? A Narrative Review

Abstract: Perinatal life represents a delicate phase of development where stimuli of all sorts, coming to or from the mother, can influence the programming of the future baby’s health. These stimuli may have consequences that persist throughout adulthood. Nuclear receptor related 1 protein (NURR1), a transcription factor with a critical role in the development of the dopaminergic neurons in the midbrain, mediates the response to stressful environmental stimuli in the perinatal period. During pregnancy, low-grade inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…At the same time, reduced functional capacity can limit the ability of the organ to adapt to an increased functional load imposed postnatally, and increase the risk for later life kidney disease, heart failure, and diabetes [ 61 ]. Specifically, current evidence shows that the developmental programming of chronic conditions, such as diabetes, cardiovascular disease, obesity, and depression, has a transgenerational effect [ 11 , 62 ] through the excessive expression of the glucocorticoid-responsive transcription factor called nuclear-receptor related 1 protein (NURR1) with environmental stress interactions during early life [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, reduced functional capacity can limit the ability of the organ to adapt to an increased functional load imposed postnatally, and increase the risk for later life kidney disease, heart failure, and diabetes [ 61 ]. Specifically, current evidence shows that the developmental programming of chronic conditions, such as diabetes, cardiovascular disease, obesity, and depression, has a transgenerational effect [ 11 , 62 ] through the excessive expression of the glucocorticoid-responsive transcription factor called nuclear-receptor related 1 protein (NURR1) with environmental stress interactions during early life [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that NR4A2 expression was higher at term compared to preterm gestation. Upregulation in placental NR4A2 has been hypothesised to be associated with inflammatory processes 21 , 44 . To further understand these changes across gestation, it would be beneficial to examine NR4A2 in first trimester placental tissue, where, if NR4A2 is involved in inflammation as hypothesised, there may be increased NR4A2 expression given many inflammatory pathways are integral in driving successful extravllous cytotrophoblast invasion and critical arteriole remodelling 20 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Nurr1 can mediate perinatal responses to stressful environmental stimuli, so epigenetic disorders involving Nurr1 in developing animals are often related to neurotoxic compounds, and they have potential intergenerational effects. 16 Many of the direct target genes of Nurr1 have been identified as essential for the cell cycle and for DNA replication during brain development. 17 There are thus reasons to suspect that Nurr1 may be a key molecule in Mel alleviating Mn-induced cell cycle arrest in NSCs.…”
Section: Introductionmentioning
confidence: 99%
“…A potential target of Mel in this regard is nuclear receptor‐related protein 1 (Nurr1), which is widely distributed in the CNS during development 15 . Nurr1 can mediate perinatal responses to stressful environmental stimuli, so epigenetic disorders involving Nurr1 in developing animals are often related to neurotoxic compounds, and they have potential intergenerational effects 16 . Many of the direct target genes of Nurr1 have been identified as essential for the cell cycle and for DNA replication during brain development 17 .…”
Section: Introductionmentioning
confidence: 99%